KOMPONEN – KOMPONEN SISTEM INFORMASI MANAJEMEN DALAM LEMBAGA PENDIDIKAN - Ramdan Abdul Malik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Management Information System (MIS) has a strategic role in improving the effectiveness and efficiency of the management of educational institutions. This research aims to identify and analyze the main components of SIM used in the educational environment. Using a qualitative method with a literature study approach, data were obtained from various literatures such as books, journals and scientific articles. The results showed that there are six main components of SIM, namely hardware, software, procedures, databases, human resources, and communication networks. Optimal integration of these components is proven to improve administrative efficiency, management transparency, and the quality of decision-making. This research emphasizes the importance of technological readiness and human resource competencies in supporting the successful implementation of SIM in educational institutions.